Tinjauan Psikologi dan Agama Terhadap Tindak Kekerasan pada Anak - Oyoh Bariah; Rina Marlina (Jurnal Studia Insania, 2019)
This study aims to analyze acts of violence on children in Karawang district and analyze acts of violence on children and their effects according to reviews of psychology and Islam. The research method used is a case study of data collected through observation, interviews, psychological tests, and documentation. Research results show that acts of violence on children in Karawang district are a form of emotional abuse and sexual violence. That is, children experience sexual deviation, sexual harassment, bullying, and depression. According to the psychological review of violence, this can affect behavior patterns later in life and according to the Islamic religion, is a violation of children's right to live, grow, and develop properly and thoroughly. The impact can affect the growth and development of a child can also shape the character and character of children in the future.